UTILIZATION OF MOBILE TECHNOLOGY AS MARKETING TOOLS IN THE DIGITAL ERA: APPLICATION & CHALLENGES - Ramadhani, Raja Almas; Maharani, Melani Defina; Ruth, Joy Noeliona; Prawira, Ida Farida Adi (Jurnal Informatika, 2023)
Human life and civilization in the 21st century have increasingly developed based on information technology. The 21st century is a century of openness or globalization; this means that human life today has undergone fundamental changes that have differed from the previous century's life system. These changes cover all aspects of life, including using mobile technology as a marketing tool. The 21st century is a digital era, where the use of digital devices, including mobile technology, is rare and difficult for today's society. This research conducts analysis using a literature review of the extent to which the utilization of mobile technology as a marketing tool is used in terms of application & challenges. This research has reviewed 44 journals from 24 countries in the sectors/industries of Agriculture, Food and drink, Education and services, Retail Business, Tours and travel, Trading Companies, and Others. The results show that mobile application companies, websites, social media, e-mail marketing, and e-commerce have utilized mobile technology as a marketing tool. However, its implementation has several obstacles and challenges; this utilization has had a positive impact and business improvement for the company's business growth.